1982
DOI: 10.1002/j.1875-9114.1982.tb03212.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology, Clinical Efficacy, and Adverse Effects of the Nonsteroidal Anti‐Inflammatory Agent Benoxaprofen

Abstract: Benoxaprofen is a nonsteroidal anti-inflammatory agent that belongs to the arylalkanoic acid class of antirheumatic drugs. Animal studies have demonstrated that it has analgesic, antipyretic, and anti-inflammatory properties. Although benoxaprofen is a relatively weak inhibitor of cyclo-oxygenase in in vitro systems, inhibits lipoxygenase in other systems, and inhibits monocyte migration in some animal models of inflammation, it has not been established that it is unique with regard to these actions. Benoxapro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…It should be noted that the glucuronidation biotransformation of the ( S )-PZQ phase I metabolites was greater than for the ( R )-PZQ phase I metabolites, which might explain why ( R )-PZQ exhibited enhanced therapeutic activity in vivo . Some studies have reported the side-effects produced by active glucuronides [3336], such as the withdrawal of benoxaprofen from world markets [37], which mainly resulted from toxicity related to hepatic metabolism via glucuronidation and the correlation between glucuronide covalent binding with proteins to the risk of idiosyncratic drug toxicity (IDT) [38]. Although the glucuronides of PZQ detected are not acyl glucuronides, the possibility of active glucuronides being generated should also be considered in the future studies of PZQ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the glucuronidation biotransformation of the ( S )-PZQ phase I metabolites was greater than for the ( R )-PZQ phase I metabolites, which might explain why ( R )-PZQ exhibited enhanced therapeutic activity in vivo . Some studies have reported the side-effects produced by active glucuronides [3336], such as the withdrawal of benoxaprofen from world markets [37], which mainly resulted from toxicity related to hepatic metabolism via glucuronidation and the correlation between glucuronide covalent binding with proteins to the risk of idiosyncratic drug toxicity (IDT) [38]. Although the glucuronides of PZQ detected are not acyl glucuronides, the possibility of active glucuronides being generated should also be considered in the future studies of PZQ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxicity in elderly patients reported for BNX was the cause of its withdrawal from the world market (Dahl and Ward, 1982). The liver was also found to be a tissue targeted by both BNX and FLX in vivo in rats (Dong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…BNX was marketed as a racemic mixture, whereas FLX was marketed as the S-isomer only. Several reports of fatal cholestatic jaundice, often associated with nephrotoxicity, led to the withdrawal of BNX from the world market only 5 months after its launch (Dahl and Ward, 1982). However, no fatal adverse events related to FLX have been reported.…”
mentioning
confidence: 99%
“…The produced covalent protein adducts increase the risk of idiosyncratic drug toxicity (IDT) including a wide range of adverse drug effects such as drug hypersensitivity reactions and cellular toxicity [39]. As a result of this metabolic pathway and its biological consequences, a number of nonsteroidal anti-inflammatory drugs cause adverse reactions in humans, as exemplified by benoxaprofen [40]. In the case of UGTs being induced or in kidney disease, the toxic glucuronides will accumulate and this will increase the risk of IDT.…”
Section: Concentration Spiked (M)mentioning
confidence: 99%